A New Species of Elianella Vercammen-Grandjean (Trombidiformes: Trombiculidae) from the Insular Equatorial Guinea with a Key to the Species into this Genus - Bassini-Silva, Ricardo; Huang-Bastos, Matheus; Welbourn, Cal; Ochoa, Ron; Barros-Battesti, Darci Moraes [UNESP]; de Castro Jacinavicius, Fernando (Springer Nature, 2021)
Purpose: The African continent has 452 chiggers (Trombidiformes: Trombiculidae) in 61 genera. One of these, Elianella Vercammen-Grandjean, 1956, has only two species known for Africa. The objective of the present study is to describe a new species for Equatorial Guinea, with the aim of increasing knowledge so scarce for Africa. Methods: In this study, we provide drawings, measurements and microscopy images on a Microscope Zeiss for the new species described below. Also, this type of the new species is deposited in the USNM. Results: We describe a new species of Elianella collected parasitizing the Bioko Forest Shrew, Sylvisorex isabellae Heim de Balsac (Eulipotyphla: Soricidae) from the insular Equatorial Guinea. Also, we are providing a key for the three species of Elianella. Conclusion: Finally, we are contributing to the knowledge of African species, due the fact this new species is the first chigger recorded to the Equatorial Guinea, on the west coast of Central Africa.
Keywords: Africa; Bioko Island; Chiggers; Ectoparasites; Endemic species; Mammals; New species